Sensing and pointing for cognitive radios using autonomous search devices - Rodriguez Colina, E.; Lopez Villaseñor, M.; Gandarilla Carrillo, O. (Visión electrónica, 2014)
This work is motivated by the monitoring function used in cognitive radio networks. To this end, two autonomous devices for searching electromagnetic signals were designed and implemented. One of them is fixed, while the other one performs the signal search to optimize the antenna pointing. The device that performs the search transmits a signal which must be returned by the other device at each position to evaluate the power. Once the search is completed, it is decided which position has the highest received signal power